Disinfection of anaerobic/aerobic sanitary effluent using ozone: Formaldehyde formation - Slompo, Nathalie Dyane Miranda; da Silva, Gustavo Henrique Ribeiro [UNESP] (Wiley, 2019)
The scarcity of natural resources supports the perspective of reusing treated effluents, mainly in agriculture, where the reduction in the demand of drinking water and the provision of alternative sources for nutrients are important. However, the process of disinfection, essential to the protection of human health, generates deleterious by-products to both humans and the environment. This research aimed to evaluate the use of ozone as a disinfectant for wastewater treated by anaerobic/aerobic baffled reactor for later agricultural reuse. Disinfection tests were conducted by applying ozone, in batch, with applied dosages of 5, 8, and 10 mg O3/L and contact time of 7 min. All the tests led to formaldehyde formation, therefore within the standard suggested by the World Health Organization. For the indicators total coliforms and Escherichia coli, the ozone was considered effective, satisfying the criteria for agricultural reuse according to the World Health Organization of a dosage of 8 mg O3/L. Practitioner Points: Proposal of decentralized system (anaerobic/aerobic baffled reactor + ozone disinfection) for effluent treatment for agricultural reuse. Formation of formaldehyde dependent on applied ozone dose. Demand of ozone consumed preferentially for the formation of by-products, with low removal of COD. High formaldehyde formation (high ozone demand) can impair the inactivation of pathogens. System promotes effluent that meets the standards established by the World Health Organization (WHO) for agricultural reuse.
Keywords: anaerobic/aerobic baffled reactor; disinfection; formaldehyde; ozone; reuse